Immunoreactivity of HOXB13 in Neuroendocrine Neoplasms Is a Sensitive and Specific Marker of Rectal Well-Differentiated Neuroendocrine Tumors - Soukup, Jiri; Manethova, Monika; Stejskal, Vaclav; Hornychova, Helena; Cesak, Tomas; Netuka, David; Ryska, Ales; Gabalec, Filip (Endocrine pathology, 2023)
HoxB13 is a transcription factor involved in defining of posterior endodermal derivatives, including prostate and rectum. While it is used as a marker of prostatic adenocarcinoma, it has not been studied systematically in neuroendocrine neoplasms. Thus, we performed HoxB13 immunohistochemistry in tissue microarrays and the whole sections of 232 neuroendocrine neoplasms. These included 34 paragangliomas (PGs), 20 cauda equina neuroendocrine tumors (CENETs), 123 well-differentiated neuroendocrine tumors (WDNETs), and 55 neuroendocrine carcinomas (NECs). WDNETs were additionally analyzed with SATB2, and colorectal WDNETs with CDX2 and serotonin immunohistochemistry. In total, HoxB13 immunoreactivity was observed in 95% (19/20) CENETs, 10.6% (13/123) WDNETs, and 12.9% (7/54) NECs. No PGs were positive. Large intestine WDNETs expressed HoxB13 in 68.4% (13/19); five negative tumors originated in cecum and one in rectum. In rectum, 92.9% (13/14) WDNETs expressed HoxB13. HoxB13 was 92.9% sensitive and 100% specific, showing 100% positive predictive value for the rectal origin of WDNET. In NECs, HoxB13 was positive in 15.4% (2/13) GIT tumors and 80% (4/5) prostatic NECs, but in none of urinary bladder NECs (0/8). SATB2 was positive in 17.1% (21/123) WDNETs, including 78.9% (15/19) of colorectal WDNETs, 71.4% (5/7) appendiceal WDNETs, and 2.9% (1/34) small intestine WDNETs. All 4 SATB2-negative large bowel tumors originated in the cecum. When both markers combined, HoxB13+/SATB2+ immunoprofile was seen exclusively in rectal WDNETs (positive predictive value 100%), while HoxB13-/SATB2+ immunoprofile was highly suggestive of the appendiceal origin (positive predictive value 71.4%). Therefore, HoxB13 can be useful as an immunohistochemical marker of rectal WDNETs and prostatic NECs.
Keywords: nádory žaludku; nádory slinivky břišní; Humans; střevní nádory; Neuroendocrine carcinoma; HoxB13; neuroendokrinní nádory; Transcription Factors; Biomarkers, Tumor; Rectal WDNET; WDNET; lidé; Intestinal Neoplasms; Neuroendocrine Tumors; Homeodomain Proteins; Carcinoma, Neuroendocrine; nádory rekta; SATB2; neuroendokrinní karcinom; nádorové biomarkery; Rectal Neoplasms; kolorektální nádory; Male; nádory močového měchýře; Pancreatic Neoplasms; homeodoménové proteiny; transkripční faktory; mužské pohlaví; Urinary Bladder Neoplasms; Stomach Neoplasms; Colorectal Neoplasms